Knowledge attainment, learning approaches, and self-perceived study burnout among European veterinary students - Iivanainen, Antti; Collares, Carlos Fernando; Wandall, Jakob; Parpala, Anna; Nevgi, Anne; Keto-Timonen, Riikka; Tipold, Andrea; Schaper, Elisabeth; van Haeften, Theo; Pihl, Tina Holberg; Press, Charles McLean; Holm, Peter (Frontiers in Veterinary Science, 2024)
Please see the abstract in the main manuscript document.